Zinc Effect on Nitrogen Fixation and Clusterbean Yield - Nandwal, A S; Dabas, S; Bharti, S; Yadav, B D (Annals of Arid Zone, 2016)
Nitrogenase activity of nodules, carbohydrate and protein contents of leaves and nodules were studied in clusterbean in response to zinc application. Zinc significantly increased the nitrogenase actitivity, carbohydrate and protein contents. At 60 days the contents of protein, carbohydrate and nitrogen were higher than at 80 days. There was some parallelism in total nitrogenase activity and nitrogen content per plant. The seed yield response to zinc as reflected in the number of pods has been discussed in relation to nitrogen fixation and dry matter production. Spray with ZnS04 proved the most effective treatment in this regard.